Exploring Microwave-Assisted Pyrolysis of Sargassum sp. for Optimal Process Parameters and Product Insights - Widawati, Teta Fathya; Refki, Muhammad Fuad; Rochmadi; Budiman, Arief (ASEAN Journal of Chemical Engineering, 2024)
Microwave-assisted pyrolysis (MAP) offers a promising alternative to fast pyrolysis for scaling up biomass conversion processes, facilitating accelerated reactions without significant temperature elevation. This study investigated the optimum process parameters for MAP of Sargassum sp., the predominant macroalgae in Indonesia. Parameters explored included Sargassum sp. particle sizes (10-40, 40-70, 70-100, >100 mesh), final temperatures (300, 350, 400, 450 °C), and coconut activated carbon (CAC)-to-feedstock ratios (1:2, 1:1, 3:2), with CAC acted as a microwave absorber. Experimental results indicated that the highest volatile yield (57.64%) occurred at a 40-70 mesh particle size and a final temperature of 450 °C, yielding bio-oil and gas at 24.88% and 32.76%, respectively. Increasing CAC loading enhanced bio-oil and char yields while reduced gas production, with a 1:1 ratio, yielded an optimal calorific value. Bio-oil density ranged from 0.9557 to 0.9968 g/mL. Gas chromatography-mass spectrometry (GC-MS) analysis revealed significant sterol derivatives and butanoic acid in the bio-oil, with lower concentrations of N-aromatic compounds. Fourier-transform infrared spectroscopy (FTIR) identified key peaks characteristic of aromatic (1400 and 1500 cm-1), carbonyl (1700 cm-1), C-N bonds (2100-2200 cm‑1), amide and amine (3300-3400 cm-1), and hydroxyl and carboxylic acid (3450 cm‑1). These findings underscored the efficacy of MAP in achieving high volatile yields at relatively moderate temperatures compared to conventional methods. Moreover, butanoic acid’s presence in the bio-oil highlighted its potential as a valuable resource for safe food preservation and chemical synthesis. However, detecting sterol derivatives and complex N-aromatic compounds suggested incomplete decomposition at 350 °C.